2016
DOI: 10.1371/journal.pone.0145984
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Association of FTO Polymorphisms with Body Mass Index in Mexicans

Abstract: To evaluate the associations between six single-nucleotide polymorphisms (SNPs) in intron 1 of FTO and body mass index (BMI), a case-control association study of 2314 unrelated Mexican-Mestizo adult subjects was performed. The association between each SNP and BMI was tested using logistic and linear regression adjusted for age, gender, and ancestry and assuming additive, recessive, and dominant effects of the minor allele. Association analysis after BMI stratification showed that all five FTO SNPs (rs1121980, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
4
39
0
8
Order By: Relevance
“…It is reported that multiple neighboring single-nucleotide polymorphisms within the first intronic region of the FTO gene are associated with BMI [21]. This is consistent with recent findings showing that different variants within the FTO gene are associated with different classes of obesity [6]. Moreover, a study by Sentinelli et al [20] showed an association between the common FTO rs9939609 polymorphism with BMI in an Italian population; however, a stronger association was observed with another polymorphism, rs9930506, within the FTO gene suggesting the impact of other polymorphisms on BMI.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is reported that multiple neighboring single-nucleotide polymorphisms within the first intronic region of the FTO gene are associated with BMI [21]. This is consistent with recent findings showing that different variants within the FTO gene are associated with different classes of obesity [6]. Moreover, a study by Sentinelli et al [20] showed an association between the common FTO rs9939609 polymorphism with BMI in an Italian population; however, a stronger association was observed with another polymorphism, rs9930506, within the FTO gene suggesting the impact of other polymorphisms on BMI.…”
Section: Discussionsupporting
confidence: 88%
“…It had been reported that the common variant rs9939609, found in the first intron of the FTO gene, is one of the most commonly replicated polymorphisms associated with obesity in both children and adults [4]. Although the association has been reported in all age groups and in both genders, inconsistency exists with studies supporting the association as being age- and gender-dependent [5, 6]. The association between FTO variants and BMI has also been reported to interact with both physical activity [7] and dietary intake [8], with physical activity attenuating the impact of FTO on BMI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9]. Several studies have further assessed the sex-dependent effects [10-13]. Moreover, novel sexual-dimorphic genetic loci have been identified via sex-stratified GWAS [7, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…В отношении ассоциаций вариантов гена FTO значи-мой оказалась половая принадлежность индивидов: для некоторых полиморфных вариантов у мужчин зареги-стрирована доминантная модель предрасположенности к ожирению, тогда как у женщин по этим же вариантам реализовывалась аддитивная или рецессивная модель предрасположенности [51]. Для мужчин и женщин с од-ними и теми же генотипами по rs9939609 гена FTO пока-зана разнонаправленная динамика изменения риска раз-вития ожирение в зависимости от числа выкуриваемых сигарет [32].…”
Section: средовые факторы модифицирующие эффекты полиморфных вариантunclassified